Mass based identification of tetracera indica chemical constituents and their anti-inflammatory activity / Fauziah Abdullah - Abdullah, Fauziah (2019)
Tetracera indica (Dilleniaceae) is locally known as mempelas. The plant grows in the forest fringes of Thailand and Peninsular Malaysia. Various parts of T. indica are traditionally used for treatment of diseases related to inflammation. However, the phytochemical data on T. indica is still lacking. Therefore, this study is focused on the phytochemistry of T. indica (stem) and evaluation of their anti-inflammatory activities. The objectives of this study are to develop LCMS/MSn method to rapidly identify the chemical constituents present in the methanol extract of T. indica stem, to isolate and characterize chemical constituents using various chromatographic and spectroscopic techniques in order to verify the LCMS/MSn method and to evaluate anti-inflammatory related biological activities of crude extract, fractions and chemical constituents of T. indica. In this work, 18 compounds mostly of the flavonoid type were detected in the HPLC profile. The methanol crude extract of the stem was analysed using two mass spectrometer systems, a QTrap 4500 and a LTQ-Orbitrap MS. With a systematic strategy combining highly resolved peaks, highly accurate mass measurements and understanding of the diagnostic fragment-based fragmentation patterns, 14 compounds from 18 peaks detected in LTQ-Orbitrap MS system were identified and characterized. They consist of six flavonol methyl ether sulphates, two dihydroflavonol methyl ether sulphates, two flavonol methyl ethers, one flavone methyl ether sulphate, one flavone aglycone, and one triterpene. The sulphated compounds were detected through neutral loss scan analysis of 80 mass unit performed on Qtrap 4500 MS system. With mass error < 2 ppm, LTQ-Orbitrap MS system confirmed identification of the sulphated flavonoids. The nine sulphated flavonoids are quercetin-3-O-sulphate 24, kaempferol 3-O-sulphate 10, quercetin-7-methyl ether-3-O-sulphate 79, kaempferol-7-methyl ether-3-O-sulphate 80, quercetin-7,4-dimethyl ether-3-O-sulphate 81, kaempferol-7,4- dimethyl ether-3-O-sulphate 84, taxifolin-3-O-sulphate 75, taxifolin-7-methyl-ether-3- O-sulphate 76 and wogonin-7-O-sulphate 82. Isolation, purification and characterization of eight compounds using spectroscopic method were done to complement and verify the mass based identification. 5,7-dihydroxy-8-methoxyflavone 28, kaempferol-7-methyl ether 14, kaempferol-7,4-dimethyl ether 7, kaempferol 6, quercetin-7-methyl ether 15 and taxifolin-7-methyl ether 85, kaempferol 4-methyl ether 83 and betulinic acid 39, were characterized by NMR spectroscopy. Occurrence of the nine sulphated compounds, six of which (75, 76, 79, 80, 81 and 82) are reported for the first time from a Tetracera species. Anti-inflammatory activities of T. indica were evaluated using xanthine oxidase and lipoxygenase inhibitory assays. The methanolic extract of the stem exhibited significant activity in both assays in a concentration dependent manner. All fractions except hexane fraction showed strong inhibitory activity against lipoxygenase in the lipoxygenase inhibitory assay. Additionally, ethyl acetate fraction showed potential inhibitory activity against xanthine oxidase and lipoxygenase enzyme. Tested at 100 ppm, 5,7-dihydroxy-8-methoxyflavone 28 and kaempferol 6 isolated from the ethyl acetate fraction inhibited lipoxygenase enzyme with 100% and 90% inhibition respectively. In addition, betulinic acid 39, kaempferol 6 and 5,7-dihydroxy-8-methoxyflavone 28, kaempferol 6, isolated from the same fraction, appeared to be the most active compounds against xanthine oxidase giving the inhibition of 95%, 90% and 80% respectively.